Clinical profile at diagnosis with youth‐onset type 1 and type 2 diabetes in two pediatric diabetes registries: SEARCH (United States) and YDR (India) - Hockett, Christine W.; Praveen, Pradeep A.; Ong, Toan C.; Amutha, Anandakumar; Isom, Scott P.; Jensen, Elizabeth T.; D'Agostino, Ralph B.; Hamman, Richard F.; Mayer‐Davis, Elizabeth J.; Lawrence, Jean M.; Pihoker, Catherine; Kahn, Michael G.; et al. (Pediatric diabetes, 2021)
Background Over the last decades, diabetes in youth has increased in both India and the United States, along with the burden of long‐term complications and healthcare costs. However, there are limited standardized population‐based data in contemporary youth cohorts for comparison of clinical and demographic characteristics of diabetes for both type 1 (T1D) and type 2 (T2D). Methods In partnership, we harmonized demographic and clinical data from the SEARCH for Diabetes in Youth (SEARCH) registry in the United States and the Registry of People with Diabetes with Youth Age at Onset (YDR) in India to the structure and terminology of the Observational Medical Outcomes Partnership Common Data Model. Data were from youth with T1D and T2D, aged <20 years and newly diagnosed between 2006 and 2010. We compared key characteristics across registries using χ2 tests and t‐tests. Results In total, there were 9650 youth with T1D and 2406 youth with T2D from 2006 to 2012. SEARCH youth were diagnosed at younger ages than YDR youth for T1D and T2D (10.0 vs 10.5 years, P < .001 and 14.7 vs 16.1 years, P < .001, respectively). For T2D, SEARCH had a higher proportion of females and significantly lower proportion of youth of high socioeconomic status compared to YDR. For T1D and T2D, SEARCH youth had higher BMI, lower blood pressure, and lower A1c compared to YDR youth. Conclusions These data offer insights into the demographic and clinical characteristics of diabetes in youth across the two countries. Further research is needed to better understand why these differences exist.